Algal biodiesel - M. M., Yusoff; Saifful Kamaluddin, Muzakir; Nurul Nadia, Abd Razak; Chin, Mei Lee; Norhayati, Nordin; Siti Aisah, Harun; Nenie Zuryati, Abdullah; Ezrinda, Mohd Zaihidee; Mohd Fazli, Farida Asras (Penerbit Universiti Malaysia Pahang, 2011)
Microalgae are unicellular photosynthetic microorganisms, living in saline or fresh water environments that convert sunlight, water and carbon dioxide to algal biomass. Microalgae species as feedstocks for biofuels (biodiesel and bioethanol) have gained considerable interest for two very reasons. First, they can be produced in areas unsuitable for crops, and secondly they can potentially grow at a much faster rate. In addition, some algae species are extremely high in lipid content, making them fit for biodiesel production. They have the potential to produce more oil per acre than any other feedstock being used to make biodiesel.